The role of museums in spreading educational and cultural awareness and its impact on visitors: a case study of Al Fahidi District Museums - Mohamed, Shaima; Abdulkarim , Maamoun (Al-Adab Journal, 2025)
Dubai is one of the UAE’s largest cities. The emirate is well-known for its rich history and heritage. As well, it has become one of the most important commercial capitals in the Arabian Gulf. Museums serve as critical institutions for the dissemination of educational and cultural knowledge, acting as bridges between the past and present. This study explores the role of the Al Fahidi District Museums in promoting cultural awareness and educational outreach, examining its impact on visitors. The Al Fahidi District Museums not only preserve the rich history of Dubai but also offer visitors a unique opportunity to engage with the emirate’s transformation from a small trading post to a global metropolis. Through a combination of qualitative and quantitative research methods, including visitor surveys, and literature reviews, this study aims to assess how effective the museum’s exhibits and programs are in enhancing visitors’ understanding of local heritage. Special attention is given to the museum’s use of interactive displays, educational workshops, and multilingual guides, which cater to a diverse audience. The findings reveal that the Al Fahidi District Museums play a significant role in shaping visitors’ perceptions of Dubai’s cultural and historical identity. Visitors reported increased awareness and appreciation for the emirate’s heritage, and the museum was praised for its ability to make history accessible and engaging. This case study underscores the importance of museums in fostering cultural understanding and highlights the need for continuous innovation in museum education programs to maximize their societal impact.